Molecular Workbench software as computer assisted instruction to aid the learning of chemistry - Khoshouie, Elaheh; Mohd Ayub, Ahmad Fauzi; Mesrinejad, Farhad (Mediterranean Center of Social and Educational Research, 2014)
This study carried out with 70 seventy secondary school students evaluated the usefulness of computer assisted instruction as an aid in the learning of chemistry in Iran. A treatment-control group design was used to test the impact of the Molecular Workbench software on students’ test performance following the use of the software package. Independent sample t-tests showed that students who were taught using the Molecular Workbench software performed better in post-tests on five chemistry topics as compared with those who received conventional instruction. Students using the software also found this software useful in the learning of chemistry.